A hyaluronic acid modified cuprous metal-organic complex for reversing multidrug resistance via redox dyshomeostasis. (1st July 2023) - Wan, Yichen; Chen, Zelong; Wang, Yi; Zhao, Wenkang; Pei, Zhichao; Pu, Liang; Lv, Yinghua; Li, Jiaxuan; Li, Jiahui; Pei, Yuxin
Abstract: Multidrug resistance (MDR) which is often related to the overexpression of P-glycoprotein (P-gp) in drug-resistant cancer cells has been a major problem faced by current cancer chemotherapy. Reversing P-gp-related MDR by disrupting tumor redox homeostasis that regulates the expression of P-gp is a promising strategy. In this work, a hyaluronic acid (HA) modified nanoscale cuprous metal-organic complex (HA-CuTT) was developed to reverse P-gp-related MDR via two-way regulated redox dyshomeostasis, which was achieved by both Cu + -catalyzed generation of OH and disulfide bonds-mediated depletion of glutathione (GSH). In vitro studies reveal that the DOX-loaded complex (HA-CuTT@DOX) has excellent targeting ability to HepG2-ADR cells due to the modification of HA and effectively induces redox dyshomeostasis in HepG2-ADR cells. Moreover, HA-CuTT@DOX can cause mitochondrial damage, decrease ATP level, and downregulate the P-gp expression, thereby leading to the reversal of MDR and the increased drug accumulation in HepG2-ADR cells. Importantly, in vivo experimental results show that it can achieve effective inhibition (89.6 %) of tumor growth in nude mice bearing HepG2-ADR cells. This is the first work to reverse P-gp-related MDR via two-way regulated redox dyshomeostasis based on a HA modified nanoscale cuprous metal-organic complex, providing a new therapeutic paradigm for effective treatment of MDR-related cancer. Graphical abstract: A hyaluronic acid modified cuprous metal-organic complex can induce the two-way regulated redox dyshomeostasis in multidrug-resistant cancer cells and ultimately reverse P-gp-related multidrug resistance. Unlabelled Image